Answer:
3x^2 + 3xz + 2y^2 - 2yz - xy
Step-by-step explanation:
(1) multiply it to get
3x^2 - 3xy + 3xz and 2yx + 2y^2 - 2yz
add similar variables (-3xy + 2yx)
( the order of the variables doesn't matter xy or yx is the same)
we get -xy
and then after that simplifying we get 3x^2 + 3xz + 2y^2 - 2yz - xy
Answer:
It is D) 4/5
Step-by-step explanation:
Answer:
4
Step-by-step explanation:
Answer:
<h2>(-1, -3)</h2>
Step-by-step explanation:
Vertex of y = |x| have the coordinates (0, 0).
f(x) + n - shift the graph n units up
f(x) - n - shift the graph n units down
f(x + n) - shift the graph n units to the left
f(x - n) - shift the graph n units to the right
nf(x) - stretches/shrinks vertically
f(nx) - stretches/shrinks horizontally
We have
f(x) = |8x + 8| - 3 = |8(x + 1)| - 3 = |8| · |x+1| - 3 = 8|x + 1| - 3
g(x) = |x| → f(x) = 8g(x + 1) - 3
vertically streched by 8 (0, 8 · 0) → (0, 0)
shifted 1 unit to the left (0 - 1, 0) → (-1, 0)
shifted 3 units down (-1, 0 - 3) → (-1, -3)